Energy aspects of acoustic cavitation and sonochemistry : fundamentals and engineering - Hamdaoui, Oualid; Kerboua, Kaouther (Elsevier, 2022)
Energy Aspects of Acoustic Cavitation and Sonochemistry: Fundamentals and Engineering covers topics ranging from fundamental modeling to up-scaled experiments. The book relates acoustic cavitation and its intrinsic energy balance to macroscopic physical and chemical events that are analyzed from an energetic perspective. Outcomes are directly projected into practical applications and technological assessments covering energy consumption, thermal dissipation, and energy efficiency of a diverse set of applications in mixed phase synthesis, environmental remediation and materials chemistry. Special interest is dedicated to the sonochemical production of hydrogen and its energetic dimensions. Due to the sensitive energy balance that governs this process, this is seen as a "green process" for the production of future energy carriers.